Prevalence of Intestinal Parasites Among Children in Various Localities of Duhok City and Nearby Villages - Mero, Wijdan M. S.; Hussein, Jehan N. (Science Journal of University of Zakho, 2013)
This study was performed from December 2008 to August 2009 to investigate the prevalence rates of intestinal parasites (intestinal protozoa and helminthes) among children of different socioeconomic classes, sexes, and age groups in Duhok city and nearby villages. A total number of 1132 stool samples were examined of ages ranging from 5 month to 13 years old. The total rate of infection, which was 27.1 %( 307), for protozoa 26.1%(295) and for helminthes 1.06%(12). In this study the following parasites were found: Giardia lamblia, Entameba histolytica, Blastocystis hominis, Entameba coli, Trichomonas hominis and Iodamoeba butschlii. The highest rate of infection was with G. lamblia 11.92% (135), followed by E. histolytica 10.15%(115), B. hominis 1.06%(12), E. coli(0.61% (7), H. nana 0.53% (6), E. vermicularis 0.35% (4), I. butschlii (0.17% (2) and T. hominis 0.08% (1). The majority of parasitic infection was single 282(24.91%), double and triple infections were very little (0.97%) and (0.08%) respectively. There was a significant difference between the rates of infection between males (29.6%) and females (22.1% (p< 0.05), significant differences ( p< 0.05) were observed between different age groups. The highest rate of infection (33.5%) was among the age group 5-7 years, followed by the age group 2-4 years , 8-10 years and infants (5 month-2 year), which were 32.8%, 28.1% and 20.4%, respectively. The lowest (15.9%) rate was recorded among the age group 11-13 years. There were significant differences (p<0.05) between the rates of infection in Heevy hospital (31.6%), rural's primary schools (25.8%) and urban’ primary schools (22.9%).